A Short-Term Exposure to Tributyltin Blocks Leydig Cell Regeneration in the Adult Rat Testis - Wu, Xiaolong; Liu, Jianpeng; Duan, Yue; Gao, Shiyu; Lü, Yao; Li, Xiaoheng; Zhu, Qiqi; Chen, Xianwu; Lin, Jing; Ye, Leping; Ge, Ren-Shan (Frontiers in Pharmacology, 2017)
Background: Tributyltin (TBT) is widely used as an antifouling agent that may cause reproductive toxicity. The mechanism of TBT on Leydig cell development is still unknown. The objective of the present study was to investigate whether a brief exposure to low doses of TBT permanently affects Leydig cell development and to clarify the underlying mechanism. Methods: Adult male Sprague Dawley rats were randomly assigned into four groups and gavaged normal saline (control), 0.1, 1.0, or 10.0 mg/kg/day TBT for a consecutive 10 days, respectively. At the end of TBT treatment, all rats received a single intraperitoneal injection of 75 mg/kg ethane dimethane sulfonate (EDS) to eliminate all of adult Leydig cells. Leydig cells began a developmental regeneration process on post-EDS day 35. The Leydig cell regeneration was evaluated by measuring serum testosterone, luteinizing hormone, and follicle-stimulating hormone levels on post-EDS day 7, 35, and 56, the expression levels of Leydig cell genes, Leydig cell morphology and number and proliferation on post-EDS day 56. Results: TBT significantly reduced serum testosterone levels on post-EDS day 35 and 56 and increased serum luteinizing hormone and follicle-stimulating hormone levels on post-EDS day 56 at ≥1 mg/kg/day. Immunohistochemical staining showed that there were fewer regenerated Leydig cells in the TBT-treated testis on post-EDS day 56. Further study demonstrated that the mRNA or protein levels of Leydig (Lhcgr, Cyp11a1, Hsd3b1, Cyp17a1, and Hsd17b3) and Sertoli cells (Fshr, Dhh, and Sox9) were significantly down-regulated in the TBT-treated testes when compared to the control. Immunofluorescent staining showed that TBT inhibited Leydig cell proliferation as judged by the reduced number of proliferating cyclin nuclear antigen-positive Leydig cells on post-EDS day 35. Conclusion: The present study demonstrated that a short-term TBT exposure blocked Leydig cell developmental regeneration process via down-regulating steroidogenesis-related proteins and inhibiting the proliferation of Leydig cells.